(untitled) (Papeles, 2019)
In the following document, we present a brief systematic search of literature on accounting theory, which is addressed or linked to the debate on theory of value. Several databases and the collaboration of professors in accounting theory from the Universidad Nacional de Colombia are used to obtain the texts to be analyzed in both Spanish and English. In each text, the development of the theory of value debate is analyzed and synthesized, seeking to evidence whether a standardization of valuation in accounting theory has been achieved through the analysis of the different positions of the authors working on this research.